The spread of anti-trafficking policies: Evidence from a new index - Seo-young Cho; Axel Dreher; Eric Neumayer (Center for Economic Studies and ifo Institute (CESifo), 2011)
We analyze the spread of policies dealing with international trafficking in human beings. Arguing that countries are unlikely to make independent choices, we identify pressure, externalities and learning or emulation as plausible diffusion mechanisms for spatial dependence in anti-trafficking policies. We develop a new index measuring governments' overall anti-trafficking policies for 177 countries over the 2000-2009 period. We also assess a country's level of compliance in the three main constituent dimensions of anti-trafficking policies - prosecution, protection and prevention. Employing a spatial autoregressive model, we find that, with the exception of victim protection measures, anti-trafficking policies diffuse across contiguous countries and main trading partners due to externality effects. We find evidence for learning or emulation effects in all policy domains, with countries looking toward peers with similar political views or cultural values. Surprisingly, major destination countries do not seem to exert pressure on relevant main countries of origin or transit to ratchet up their policies.
Keywords: O15; F22; P41; 330; human trafficking; human rights; spatial dependence of policies